2003
DOI: 10.1172/jci200317959
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of inward rectifier current in heart probed by Kir2.1 overexpression and dominant-negative suppression

Abstract: The inward rectifier current IK1 is tightly regulated regionally within the heart, downregulated in heart failure, and genetically suppressed in Andersen syndrome. We used in vivo viral gene transfer to dissect the role of IK1 in cardiac repolarization and maintenance of the resting membrane potential (RMP) in guinea pig ventricular myocytes. Kir2.1 overexpression boosted Ba2+-sensitive IK1 by more than 100% (at –50mV), significantly shortened action potential durations (APDs), accelerated phase 3 repolarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(63 citation statements)
references
References 28 publications
5
57
0
Order By: Relevance
“…Biological pacemakers can be derived from gene and cell therapy [1]. During the past few years, several gene therapy strategies have been devised [2,3,4,5,6,7,8], but the changes of receptors or channels caused by local or whole area transfection of myocardium can be proarrhythmic [9, 10]. Moreover, the genes employed in these efforts have not been pivotal modulators of spontaneous depolarization in sinoatrial node (SAN) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Biological pacemakers can be derived from gene and cell therapy [1]. During the past few years, several gene therapy strategies have been devised [2,3,4,5,6,7,8], but the changes of receptors or channels caused by local or whole area transfection of myocardium can be proarrhythmic [9, 10]. Moreover, the genes employed in these efforts have not been pivotal modulators of spontaneous depolarization in sinoatrial node (SAN) cells.…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac myocytes, I K1 sets the resting membrane potential, controls the approach to threshold upon depolarization, and modulates the terminal phase of repolarization (Lopatin & Nichols, 2001; Miake et al . 2003).…”
mentioning
confidence: 99%
“…I Kir flows through tetrameric channels formed by subunits in the Kir2 family (Kir2.1–2.4). The polyamine block of Kir2 channels has been studied mainly using Kir2.1, which may be the predominant subunit mediating the cardiac I Kir (Zaritsky et al 2001; Miake et al 2003). Studies have shown that block of the outward currents by internal particles involves both high‐ and low‐affinity block (Yang et al 1995 a ; Guo & Lu, 2000), but the molecular mechanisms for two types of block, and the physiological relevance of the low‐affinity block, remained unclear.…”
mentioning
confidence: 99%